(untitled) (Bioresearch Communications, 2026)
Background: Trans fatty acids (TFAs) found in partially hydrogenated vegetable oils (PHOs) are a significant health risk factor for cardiovascular diseases. Despite global initiatives to minimize TFAs, including the WHO’s REPLACE action framework, data on their content in Bangladeshi food products remains limited. This study assessed the trans-fat content in PHOs available in the Dhaka City market, which will be beneficial in providing critical baseline data for public health interventions. Methods: The study involved market surveys of four wholesale and nine retail markets across Dhaka to identify PHO brands. A total of 20 PHO samples representing four major brands and their various batches were collected from both retail and wholesale markets. Samples were analyzed for fatty acid composition, including saturated, monounsaturated, polyunsaturated, and trans fatty acids, using gas chromatography with flame ionization detection (GC-FID) according to the AOAC Official Method 996.06. Additionally, the probable intake of TFA through PHO consumption and its contribution to the percentage of the daily allowable intake were estimated. Results: According to our findings, PHOs were mainly used by bakeries and restaurants. The mean trans-fat content of the samples was 10.20 ± 2.39 g per 100 g, with all samples exceeding the WHO recommended limit of 2%. TFA levels varied significantly across brands, ranging from 7.64±0.71 to 13.39 ± 2.85 g per 100 g. Saturated fatty acids (SFA) constituted 57.10 ± 3.55g per 100 g, while monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids were 38.87 ± 4.97 g and 4.03 ± 1.51 g, respectively. If consumed at a level similar to 50% of average oil intake (15.4 g/day), PHOs would contribute 67.5% of the WHO’s recommended daily TFA limit (2.2gday) and 40% of the SFA limit (22.22g/day). Conclusion: The PHOs sold in Dhaka contain high levels of trans fats, posing serious public health risks. Urgent regulatory action, such as enforcing WHO-recommended TFA limits or banning PHOs, is needed to reduce and ultimately eliminate industrially produced TFAs from the Bangladeshi food supply chain. Bioresearch Commu. 12(1): 2035-2042, 2026 (January)